Changes in the incidence and prevalence of type 1 and type 2 diabetes among 2 million children and adolescents in Hungary between 2001 and 2016 – a nationwide population-based study - László Barkai (Termedia Publishing House, 2019)
Introduction The aim of the present study was to assess changes in the incidence and prevalence of type 1 diabetes (T1DM) and type 2 diabetes (T2DM) in children and adolescents in Hungary during the period 2001 to 2016 in order to provide nationwide population-based epidemiology data on diabetes in youths aged 0–18 years.